Association Between SHBG Levels and Hypertensive Disorders of Pregnancy: A Systematic Review and Meta‐Analysis - Ajay Malvi; Muhammed Shabil; Mahalaqua Nazli Khatib; Roopashree R; Mandeep Kaur; Manish Srivastava; Amit Barwal; G. V. Siva Prasad; Pranchal Rajput; Rukshar Syed; Kamal Kundra; Vinamra Mittal; et al. (The Journal of Clinical Hypertension)
ABSTRACT Sex hormone‐binding globulin (SHBG) regulates sex hormone availability and is influenced by metabolic factors. Variations in SHBG levels during pregnancy may affect the development of hypertensive disorders such as gestational hypertension (GH) and preeclampsia (PE). This systematic review and meta‐analysis explores the potential of SHBG as a biomarker for predicting GH and PE. A search of PubMed, Embase, and Web of Science was conducted to identify studies evaluating the association between SHBG levels and the risk of HDP, including GH and PE. Inclusion criteria encompassed observational studies reporting quantitative risk estimates (risk ratios, odds ratios, or hazard ratios) for SHBG levels. Results were pooled using a random‐effects meta‐analysis in R software (V 4.4), with the I2 statistic assessing heterogeneity. Eight studies were included in the systematic review from a total of 592 screened records. The association between SHBG levels and the risk of any HDP showed a pooled OR of 0.875 (95% CI: 0.772–0.993), for PE 0.890 (95% CI: 0.767–1.032), and for GH 0.729 (95% CI: 0.442–1.205), suggesting significant association between SHBG and HDP. Sensitivity analysis validated the robustness of the findings. This meta‐analysis found potential significant association between higher SHBG levels and risk of HDP. Further high‐quality research is required to better understand the role of SHBG in pregnancy‐related hypertensive disorders. Future studies should consider larger sample sizes, more precise measurement techniques, and explore potential confounding factors to clarify the potential utility of SHBG as a biomarker for predicting GH and PE.